Microbe Profile: Buchnera aphidicola: ancient aphid accomplice and endosymbiont exemplar. Issue 12 (23rd December 2021) - Moran, Nancy A.
Abstract : Buchnera aphidicola is an obligate endosymbiont of aphids that cannot be cultured outside of hosts. It exists as diverse strains in different aphid species, and phylogenetic reconstructions show that it has been maternally transmitted in aphids for >100 million years. B. aphidicola genomes are highly reduced and show conserved gene order and no gene acquisition, but encoded proteins undergo rapid evolution. Aphids depend on B. aphidicola for biosynthesis of essential amino acids and as an integral part of embryonic development. How B. aphidicola populations are regulated within hosts remains little known.